Web-based idea management and Quadruple Helix networking of creative industry cohorts for COVID-19 - Mikelsone, Elina; Babris, Matijs; Segers, Jean-Pierre; Beitane, Alina; Babre, Andra Marta (Business: Theory and Practice, 2024)
On the one hand, web-based idea management platforms such as IdeaScale, Spigit, and BrightIdea can be used to facilitate the sharing of ideas and insights from existing EU and international cohorts of relevance to COVID-19. These platforms can be used to capture ideas from the experts, employees, public and other stakeholders (internal and external), and to facilitate the exchange of ideas and insights in a structured and organized way. On the other hand, Quadruple Helix networking can be used to facilitate collaboration and knowledge sharing between existing EU and international cohorts of relevance to COVID-19. This approach involves bringing together four key stakeholders – government, industry, academia, and civil society – to work together to develop solutions to the grand societal challenges posed by the pandemic. In this paper authors will fill the gap between web-based IMS practical application and theoretical framework of Quadruple Helix model to demonstrate potential benefits of merging of these elements. To bridge the gap systematic and analytical literature review will be done to create new Quadruple Helix web-based IMS framework and demonstrate it in action with case study taken from the creative industry. Aim of the research: potential of web-based idea management application in Quadruple Helix context in networking of existing EU and international cohorts of relevance to COVID-19. To reach the aim this research uses a combination of literature review, action-based research, and descriptive analysis to analyse the data and draw conclusions. Main conclusions: proves the potential of web-based IMS application with Quadruple Helix context. The application of the web-based IMS and Quadruple Helix approach is holistic and adaptable. Authors have created Quadruple Helix Adaptation in Idea Management Application Framework by including elements such as: Application elements includes: P1 is idea generation process, P2 is idea evaluation, P3 continuation of IM; Adaptation elements includes Quadruple Helix approach partners: Q1: universities, Q2: civilians; Q3: businesses; Q4: government.